Viroid ecology in hops (Humulus lupulus L.): high prevalence in commercial systems but low presence in wild populations - Jagani, Swati; Krönauer, Christina; Born, Ute; Hagemann, Michael Helmut (Frontiers in Microbiology, 2026)
IntroductionHop (Humulus lupulus L.), a vital crop in the brewing industry, is increasingly threatened by infections caused by viroids and viruses. The extensive use of vegetative propagation in hop cultivation facilitates the accumulation and dissemination of these pathogens. However, little is known about their prevalence and ecological behavior in non-commercial settings. This study provides a comprehensive overview of viroid and virus infections across Germany, with particular attention to their occurrence and potential transmission across commercial, settlement, and wild hop populations.MethodsBetween 2020 and 2023, 418 hop leaf samples from commercial (n = 345), settlement (n = 29), and wild (n = 44) populations were collected. Viroid and virus detection was performed using RT-PCR and PCR. To investigate possible cross-species transmission and sequence variation, HSVd-positive samples from hops and nearby grapevines were further analyzed via Sanger sequencing.ResultsViroid screening revealed that the citrus bark cracking viroid (CBCVd; Cocadviroid rimocitri) was confined to commercial hop cultivation. This study also marks the first confirmed detection of hop stunt viroid (HSVd; Hostuviroid impedihumuli) in commercial hop fields in Germany. Virus screening showed that hop latent virus (HpLV; Carlavirus latenshumuli) and american hop latent virus (AHpLV; Carlavirus americanense) were exclusively found in commercial hops. Hop mosaic virus (HpMV; Carlavirus humuli) was detected across all three groups—commercial, settlement, and wild populations. Arabis mosaic virus (ArMV; Nepovirus arabis) and apple mosaic virus (ApMV; Ilarvirus ApMV) were identified in both commercial and wild hops but were absent from settlement samples. Overall, commercial hop populations exhibited the highest pathogen burden, frequently harboring multiple viroid and virus infections. These findings underscore the importance of using certified, pathogen-free planting material, implementing early detection strategies, and updating plant passport regulations to include high-risk pathogens. While prevalence estimates reflect risk-based sampling from key production regions, the study provides a solid basis for enhancing pathogen surveillance and improving preventive measures in hop cultivation.